The law of consumer protection and fair trading - Harvey, Brian W. (London : Butterworths, 1982)
This book expresses a body of law protecting the private consumer form unsafe products, qualitative deficient goods and services and fraudulent trading practices.
Included bibliographical index
mf 25/01/2019
Loans
Keywords: Consumer protection; Trade regulation; London